PENGARUH INKLUSI, LITERASI, DAN PENGELOLAAN KEUANGAN TARHADAP KINERJA UMKM SEKTOR KULINER DI KABUPATEN PANGKAJENE DAN KEPULAUAN - Sri Ayu; Risal Risal (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the Influence of Inclusion, Literacy and Financial Management on the Performance of MSMEs in the Culinary Sector in Pangkajene and Kepulauan Regency. The respondents in this study were 50 MSMEs in the culinary sector. This study uses data collection by distributing questionnaires to respondents. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear regression tests, and partial tests (t-tests) were used with the help of the SPSS 25 application. The test results show that: 1). Partially, the Inclusion variable obtained a t-value of -0.737 <t table 2.014 and a significant value of 0.465> 0.05. So it can be concluded that Ho is accepted and Ha is rejected, so it means that Inclusion has a negative and insignificant effect on the Performance of MSMEs in the Culinary Sector. 2). The Literacy variable obtained a t-value of 3.122> t table 2.014 and a significant value of 0.003 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, so it means that Literacy has a positive and significant effect on the Performance of MSMEs in the Culinary Sector. 3). The Financial Management variable obtained a t-value of 2.145> t table 2.014 and a significant value of 0.037 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, so it means that Financial Management has a positive and significant effect on the Performance of MSMEs in the Culinary Sector.